Dawne nazwy astrologii i astrologów - Krótki, Zuzanna (Forum Lingwistyczne, 2015)
The ancient names of the astrology and the astrologers The article is trying to analyse in a semantic way the former names of astrology and the star gazers. The material gathered from all available wells of information; lexicographical sources containing the texts from the fourteen century to the eighteen one. It is manifested in a way that the astrological vocabulary of the old Polish differed from the contemporary lexicology. The changes which occurred on this level of language had an additional „character of quantity” – from the ample collection of 18 units were left barely 2 lexems – astrologia and astrolog. Beside the point there was another character – “the quality character” (the semantic one). At the beginning “the investigated terrain” was affiliated with the category of ASTRONOMY. That is why a lot of names of astrology and the “star watchers” swerved back and forth for long at the stitch of two lexical fields similar semantically. Overall changes which took place in the investigated word-group are reflections of moving trends in societal and cultural spheres of the years gone by. Key words: the changes in meanings, the history of Polish language, nomination, semantics